Anti Fungal Activity of Chitinolytic Bacteria Lysinibacillus fusiformis and Brevibacillus reuszeri Against The Fungal Pathogens Rhizoctonia solani and Fusarium oxysporum - Mashuri Masri; Eka Sukmawaty; As Awalia Amir (Microbiology Indonesia, 2021)
Abstract. Chitinolytic bacteria can produce chitinase, reported as a biocontrol agent against plants. This research aims to see chitinolytic activity in inhibiting the growth of Rhizoctonia solani and Fusarium oxysporum. Anti fungal testing in dual culture test by growing each of the chitinolytic bacteria, Lysinibacillus fusiformis and Brevibacillus reuszeri, with the pathogenic fungi, F. oxysporum and R. solani, in Petri dishes containing Chitin Agar Media facing a distance of 3 cm. The results showed that chitinolytic bacterial isolates were capable inhibit the fungus by having the activity of each index inhibition of L. fusiformis isolates (30%), B. reuszeri (77%) against F. oxysporum, and R. solani fungi isolates (100%) for each chitinolytic bacterial isolate. Keywords : Anti fungal, Chitinolytic bacteria, Pathogenic fungi.